KEBIJAKAN FORMULASI PERDAGANGAN PENGARUH (TRADING IN INFLUENCE) SEBAGAI PERBUATAN MELAWAN HUKUM DALAM TINDAK PIDANA KORUPSI - Adinda KInanthi Nusantari Madania (2021)
From time to time, modus operandi of corruption crimes has undergone a significant change. This can be proven by the existence of various types of corruption, one of which is Trading in Influence which has been regulated in the United Nations Convention Against Corruption (UNCAC) but its implementation has not been fully realized in Indonesian criminal law. In fact, corruption is an act against the law that violates the law, harms the state and disturbs the welfare of society. The purpose of this study is to find out and examine how the practice of criminalizing influence trading in Indonesia and the policy of criminalizing influence trading as an act against the law in corruption in Indonesia. Based on this, the writing of this journal raises the following problems: 1) How is the arrangement of Trading In Influence according to the prevailing laws and regulations in Indonesia? and 2.) How to formulate a trading in influence policy in the future? The method used in this research is normative research with a qualitative approach so as to produce a descriptive analytical research. The results of the study explain that this legal vacuum causes law enforcement officers to often use bribery offenses, even though bribery and Trading in Influence do not have the same meaning and the imposition is limited to civil servants or state officials. Meanwhile, the concept of the formulation of trading in influence arrangements is being discussed in the RKUHP. Keywords: Formulation Policy, Trading in influence, Tort Law